On the interrelationship between linguistics and philosophy in Eugenio Coseriu’s scientific thinking - Serena, Araceli López (Scandinavian Studies in Language, 2023)
This article aims to show how closely interrelated philosophy and linguistics are in Eugenio Coseriu’s scientific thinking. It argues that Synchrony, Diachrony and History (SDH), one of the author’s major works, cannot be conceived as a mere treatise on the problem of linguistic change, but needs to be recognised as a fundamental work for unravelling the epistemological principles that underpin the philosophical-scientific edifice of Coseriu’s linguistic theory. Based on SDH, it will be shown how, in this work, Coseriu insists on the errors of the approach and method that the causalist perspective promotes, how he advocates for the differentiation between natural sciences and human sciences and the consequent application, in the latter, of a finalist perspective, and finally how he describes the epistemic activities involved in resorting to the original knowledge or intuition that the linguist has as a speaker of the language under study.